2023
DOI: 10.1126/sciadv.add6167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an aqueous, air-stable, superconducting 1T′-WS 2 monolayer ink

Abstract: Liquid-phase chemical exfoliation can achieve industry-scale production of two-dimensional (2D) materials for a wide range of applications. However, many 2D materials with potential applications in quantum technologies often fail to leave the laboratory setting because of their air sensitivity and depreciation of physical performance after chemical processing. We report a simple chemical exfoliation method to create a stable, aqueous, surfactant-free, superconducting ink containing phase-pure 1T′-WS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Synthesis of K 0.5 WS 2 K 0.5 WS 2 was synthesized by high-temperature solid-state methods reported previously; its crystal structure and chemical composition were reported in the same paper …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of K 0.5 WS 2 K 0.5 WS 2 was synthesized by high-temperature solid-state methods reported previously; its crystal structure and chemical composition were reported in the same paper …”
Section: Methodsmentioning
confidence: 99%
“…Examples include gated WTe 2 monolayers, , bulk WTe 2 under pressure, , strained thin flakes of WTe 2 , bulk MoTe 2 in its 1T′ phase, and 1T′-MoS 2 monolayers. , Out of these, 2M-WS 2 has the highest superconducting transition temperature. 2M-WS 2 has been chemically exfoliated to monolayers, and thin films composed of many overlapping monolayers were shown to superconduct below 7.3 K …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the experimental EXAFS spectrum of the product was fitted perfectly with the theoretical spectrum for 1T′-WS 2 (Figure k). The successful preparation of the 1T′-TMD bulk crystals enabled the large-scale preparation of 1T′-TMD nanosheets by using the chemical intercalation and exfoliation method. , For example, Peng et al . reported that the 1T′-MoS 2 monolayers with a size of up to tens of micrometers can be prepared by the exfoliation of the millimeter-sized 1T′-MoS 2 crystal synthesized by the gas-solid reaction method …”
Section: Phase Engineering In Transition Metal Dichalcogenide (Tmd) N...mentioning
confidence: 99%
“…Liquid-mediated exfoliation is believed to be a viable method for producing nanosheets on a large scale. The ability to use these colloidal nanosheet suspensions to produce air-stable inks or thin films has generated significant interest in the approach and its potential . However, before the process can be scaled up, several conditions must be considered, such as solvent selection, sonication power, time, and the use of additives.…”
Section: Production and Fabrication Of 2d Materialsmentioning
confidence: 99%